Latitudinal selectivity of foraminifer extinctions during the late Guadalupian crisis. Issue 4 (8th April 2009) - Bond, David P. G.; Wignall, Paul B.
Abstract : A global database of middle–upper Permian foraminiferal genera has been compiled from the literature for 75 Guadalupian and 62 Lopingian localities, grouped into 32 and 19 operational geographical units respectively. Cluster analysis reveals that five distinct Guadalupian provinces were reduced to four in the Lopingian, following the disappearance of the Eastern Panthalassa Province. Extinction magnitudes across the Guadalupian/Lopingian (G/L) boundary reveal that, in the remaining provinces, there is a strong regional variation to the losses at low paleolatitudes. The Central and Western Tethys Province experienced a markedly lower extinction magnitude, at both provincial and global levels, than the Eastern and Northern Tethys Province. Panthalassa experienced a high extinction magnitude of endemics, but a global extinction magnitude similar to that recorded in Central and Western Tethys. This regional bias is seen in both the fusulinacean and non-fusulinacean foraminifera, although fusulinaceans suffered much higher magnitudes of extinction. The regional selectivity also persisted during the subsequent Lopingian radiations, with the Central and Western Tethys Province recording the greatest magnitudes. Thus, of 35 new genera recorded globally from the Lopingian, 27 of these are recorded in Central and Western Tethys, compared to five and 12 genera respectively in Panthalassa and in Eastern and Northern Tethys. The Emeishan large igneous province erupted within the Eastern and Northern Tethys Province and may have been a factor in the high extinction–low radiation regime of this region. Regression (and consequent shallow-marine habitat loss) also appears to have been a significant factor. A major, but brief, late Guadalupian regression is best seen in those areas that suffered the greatest extinction losses.